2014
DOI: 10.9738/intsurg-d-13-00118.1
|View full text |Cite
|
Sign up to set email alerts
|

Glasgow Prognostic Score (GPS) Can Be a Useful Indicator to Determine Prognosis of Patients With Colorectal Carcinoma

Abstract: The Glasgow Prognostic Score (GPS), an inflammation-based score, has been used to predict the biologic behavior of malignant tumors. The aim of the current study was to elucidate a further significance of GPS in colorectal carcinoma. Correlation of GPS and modified GPS (mGPS), which are composed of combined score provided for serum elevation of C-reactive protein and hypoalbuminemia examined before surgical treatment, with clinicopathologic features was investigated in 272 patients with colorectal carcinoma. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 23 publications
2
37
0
Order By: Relevance
“…Therefore, mGPS is 0 in the case of low albumin and low CRP (35). There are several studies, including recent meta-analysis, which indicate a clear association between high GPS and mGPS and poor OS and CSS irrespective of TNM stage and tumour differentiation (41)(42)(43)(44)7).…”
Section: Systemic Inflammation Markers In Crcmentioning
confidence: 99%
“…Therefore, mGPS is 0 in the case of low albumin and low CRP (35). There are several studies, including recent meta-analysis, which indicate a clear association between high GPS and mGPS and poor OS and CSS irrespective of TNM stage and tumour differentiation (41)(42)(43)(44)7).…”
Section: Systemic Inflammation Markers In Crcmentioning
confidence: 99%
“…In chemo-naïve mCRC, Lin et al showed, using a sample size of 488 patients, that patients with high pre-chemotherapy LMR (≥3.11) experienced significant improvement in PFS (9.2 vs. 7.6 months, p < 0.001) and OS (19.4 vs. 16.6 months, p < 0.001) compared with patients with low pre-chemotherapy LMR. These results were also seen in the setting of resectable CRC, as a recent study published in March 2017 showed an independence of LMR in being a predictive factor of survival [ 59 ]. The study had a huge sample size of 1623 with a cut-off value of LMR 2.38.…”
Section: Literature Reviewmentioning
confidence: 75%
“…However, there is no consensus with regard to reduced SSI incidence or prolonged survival, and the effects of early introduction or co-administration with antitumor therapies, such as molecular targeted therapy, are anticipated in the future 23 . Cachexia was once regarded as an irreversible condition, but given that a reduction in the activity of inflammation-induced substances and suppression of inflammatory cytokine production could be achieved by initiating nutrition therapy before the patient falls into an intractable state of cachexia, active multimodal therapy may prove effective 24 .…”
Section: Discussionmentioning
confidence: 99%